WYKLUCZENIE SPOŁECZNE W KONTEKŚCIE UBÓSTWA I BEZDOMNOŚCI - Nogowski, Jacek Marek (Civitas et Lex, 2015)
The social exclusion is impossibilities determined in categories of participating in relevant aspects of the, economic, political social life and the cultural given society. The poverty is being related to persons, families or groups of people, of which resources (financial, cultural and social) they are limited in such a step, that the level of their life is lowering beyond the accepted minimum in the country of residence. A homelessness is both a cause and effect of other states of the poverty, lack of motivation, rejecting moral norms, lack of the ability, too pathological having socially recognised features. A poverty and a homelessness are one of social important issues of contemporary world which requires preventive concrete actions preventing of coming into existence of this phenomenon in order not to lead to the social exclusion.